Export Market-oriented Activities: Their Antecedents and Performance Consequences - Cadogan, John W.; Diamantopoulos, Adamantios; Siguaw, Judy A. (Journal of International Business Studies, 2002)
This paper extends the study of market orientation into the international arena by developing and testing hypotheses relating to the antecedents to and consequences of market-oriented activities in firms’ export operations. Export experience, export dependence and coordinating capabilities were found to be positively related to export market-oriented activities. In turn, export market-oriented activities were positively associated with aspects of export performance.